2020
DOI: 10.2147/tcrm.s230592
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inclisiran for the Treatment of Cardiovascular Disease: A Short Review on the Emerging Data and Therapeutic Potential</p>

Abstract: Proprotein convertase subtilisin kexin 9 (PCSK-9)-targeting therapy has arisen as a new line for the treatment of hyperlipidemia. Inclisiran is a double-stranded small RNA molecule that works by blocking the transcription of PCSK-9, leading to a reduction of PCSK9 levels in the hepatocytes, resulting in an increased expression of low-density lipoprotein (LDL) receptors in the hepatocyte membrane and, as a consequence, it reduces the circulating levels of LDL cholesterol (LDL-C). Compared to the other LDL-C-low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…Inclisiran is a relatively new drug that was authorized for use by the European Medicines Agency in December 2020. It is a silencing RNA (siRNA) particle targeting the hepatic production of PCSK9 [ 86 ]. Inclisiran selectively interferes with the expression of specific genes and catalytically silences the translation of the complementary target messenger RNA (mRNA), blocking the synthesis of PCSK9 [ 86 ].…”
Section: Pcsk9 and Pcsk9 Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inclisiran is a relatively new drug that was authorized for use by the European Medicines Agency in December 2020. It is a silencing RNA (siRNA) particle targeting the hepatic production of PCSK9 [ 86 ]. Inclisiran selectively interferes with the expression of specific genes and catalytically silences the translation of the complementary target messenger RNA (mRNA), blocking the synthesis of PCSK9 [ 86 ].…”
Section: Pcsk9 and Pcsk9 Inhibitorsmentioning
confidence: 99%
“…It is a silencing RNA (siRNA) particle targeting the hepatic production of PCSK9 [ 86 ]. Inclisiran selectively interferes with the expression of specific genes and catalytically silences the translation of the complementary target messenger RNA (mRNA), blocking the synthesis of PCSK9 [ 86 ]. Clinical trial data showed a 44% reduction in LDL-C level compared to placebo in heterozygous FH, and a 50% reduction in general hypercholesterolemic patients [ 87 , 88 ].…”
Section: Pcsk9 and Pcsk9 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported mechanism of action is reduction of intra and extracellular production of PCSK9, from conjugation with triantennary N-acetylgalactosamine (GalNAc) that provides high-affinity binding to hepatocyte receptors, which reduce the dose and volume of drug required and the highly specific liver uptake should result in less chance of off-target effects. 13,14 Efficacy on LDL-C reduction has been demonstrated in phase II and III ORION studies, with participation of more than twenty thousand patients worldwide, 14 who were under maximum dosing of statins and/or more ezetimibe and with significant risk factors for cardiovascular disease, achieving a reduction in LDL-C of approximately 50%, allowing up to six months between doses.…”
Section: Innovative Approved Moleculesmentioning
confidence: 99%
“…On the other hand, other potential therapeutic strategies targeting PCSK9 are in development, including inclisiran (a small interfering RNA [siRNA] molecule), other small molecule inhibitors that disrupt the processing of PCSK9, as well as adnectins, which block the binding of PCSK9 to the LDLR. [71][72][73]…”
mentioning
confidence: 99%